Application of Imprecise Decision Modeling for Regional Development Policies in Indonesia - Novita Erlinda; Akhmad Fauzi; Slamet Sutomo; Eka Intan Kumala Putri (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2016)
Regional Development encompasses many aspect of economic, social, and environmental attributes. In the context of developing country, the decision to fulfill these attributes are often hindered by lack of clear development scenarios and constraints. This study is an attempt to capture the complexity of decision makers for regional development scenarios using imprecise decision modeling (IDM) by incorporating imprecise information and uncertainties. A series of social, economic and environmental criteria based on agreement from multi stakeholders dialogues were developed along with four policy development scenarios. Results from such a modeling provides variety of decision alternatives based on probabilities and risk assessment associated with achieving policy objectives.